2015
DOI: 10.1177/0961463x15577264
|View full text |Cite
|
Sign up to set email alerts
|

What makes successful entrepreneurs different in temporal and goal-commitment dimensions?

Abstract: Purpose: The article is an attempt to identify, with respect to temporal and goal-commitment dimension (effort, persistence, goal satisfaction), the characteristics of entrepreneurs in different stages of the entrepreneurial process (the prelaunch and postlaunch phases) and to indicate the differences between entrepreneurs and nonentrepreneurs.Methodology: To answer this question, data from three samples were collected. Actual (N ¼ 127) and nascent (N ¼ 344) entrepreneurs filled questionnaires: the Scale of En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…As opposite relationships-from success to work engagement and positive orientation-have also been confirmed, this suggests that (self-)appreciation of success, rewarding what has already been achieved may help to change these successes into motivational cues for future actions leading to personal resources gains (Gorgievski and Hobfoll 2008;Hobfoll 1989). As entrepreneurs tend to be future-oriented (Przepiorka 2016), such appreciation of successes achieved and celebration of what has already been done may not be easy for them. Therefore, this needs to be planned in advance.…”
Section: Implications For Practicementioning
confidence: 99%
“…As opposite relationships-from success to work engagement and positive orientation-have also been confirmed, this suggests that (self-)appreciation of success, rewarding what has already been achieved may help to change these successes into motivational cues for future actions leading to personal resources gains (Gorgievski and Hobfoll 2008;Hobfoll 1989). As entrepreneurs tend to be future-oriented (Przepiorka 2016), such appreciation of successes achieved and celebration of what has already been done may not be easy for them. Therefore, this needs to be planned in advance.…”
Section: Implications For Practicementioning
confidence: 99%
“…One study reports that psychological capital is negatively related to entrepreneurs' levels of perceived stress (Baron et al, 2016). Such individual-level characteristics are likely more important at the beginning of the entrepreneurial process than during the later stages (Przepiorka, 2016).…”
Section: The Entrepreneurial Process As Affected By Stress Processes:mentioning
confidence: 99%
“…Goal commitment, on the other hand, has been studies and verified to be important at different stages of the entrepreneurial process (Przepiorka, 2016). Empirical studies have found out that entrepreneurial role models (i.e., parents) not only predicted entrepreneurial intentions (Geldhof et al, 2014;Schmitt-Rodermund, 2004), but also the development of entrepreneurship (Bosma et al, 2012;McClelland, 1961).…”
Section: The Mediation Of Goal Commitmentmentioning
confidence: 99%
“…Przepiorka (2016) identified the differences between entrepreneurs and non-entrepreneurs with respect to goal-commitment (effort, persistence, goal satisfaction) and found out that entrepreneurs with greater goal-commitment (who put in more effort and were more persistent and satisfied with their goals) during the prelaunch phase of the entrepreneurial process had greater intention to succeed.…”
Section: The Mediation Effect Of Goal Commitmentmentioning
confidence: 99%
See 1 more Smart Citation